WRF High Resolution Dynamical Downscaling of Precipitation for the Central Andes of Chile and Argentina - Schumacher, Vanucia; Fernández, Alfonso; Justino, Flavio; Comin, Alcimoni (Frontiers in Earth Science, 2020)
This study evaluates the capabilities of the Weather Research and Forecasting (WRF) model to reproduce the variability of precipitation over Central Andes of Chile and Argentina, a region characterized by complex topography. The simulation corresponds to a dynamical downscaling of ERA-Interim, in the period 1996–2015, performed with two nested grids, at 9 and 3 km horizontal resolution. Precipitation data from 62 rain gauges from Chile and Argentina were used to evaluate the performance of WRF simulations carried out at the annual and warm-cold season analysis. The results of this study indicate that WRF at 9 km and 3 km is able to reproduce the main characteristics of precipitation, seasonal and interannual variability along the study area. However, WRF at 9 km presents a wet bias in relation to observation and WRF at 3 km along the windward slopes of the Andes. Additionally, WRF at 3 km achieves better performance of precipitation as elevation increases, most likely due to the better-resolved orography.